Conductive, Solution‐Processed Dioxythiophene Copolymers for Thermoelectric and Transparent Electrode Applications. Issue 24 (6th May 2019) - Ponder, James F.; Menon, Akanksha K.; Dasari, Raghunath R.; Pittelli, Sandra L.; Thorley, Karl J.; Yee, Shannon K.; Marder, Seth R.; Reynolds, John R.
Abstract: Conjugated polymers with high electrical conductivities are attractive for applications in capacitors, biosensors, organic thermoelectrics, and transparent electrodes. Here, a series of solution processable dioxythiophene copolymers based on 3, 4‐propylenedioxythiophene (ProDOT) and 3, 4‐ethylenedioxythiophene (EDOT) is investigated as thermoelectric and transparent electrode materials. Through structural manipulation of the polymer repeat unit, the conductivity of the polymers upon oxidative solution doping is tuned from 1 × 10 −3 to 3 S cm −1, with a polymer consisting of a solubilizing alkylated ProDOT unit and an electron‐rich biEDOT unit (referred to as PE2 ) showing the highest electrical conductivity. Optimization of the film casting method and screening of dopants result in AgPF6 ‐doped PE2 achieving a high electrical conductivity of over 250 S cm −1 and a thermoelectric power factor of 7 μW m −1 K −2 . Oxidized spray cast films of PE2 are also assessed as a transparent electrode material for use with another electrochromic polymer. This bilayer shows reversible electrochemical switching from a colored charge‐neutral state to a highly transmissive color‐neutral, oxidized state. These results demonstrate that dioxythiophene‐based copolymers are a promising class of materials, with ProDOT–biEDOT serving as a soluble analog to the well‐studied PEDOT as a p‐type thermoelectric and electrode material. Abstract : Solution processable dioxythiophene copolymers based on 3, 4‐propylenedioxythiophene and 3, 4‐ethylenedioxythiophene are investigated. Through structural manipulation of the polymer repeat unit and optimization of the film casting and doping process, the conductivity is enhanced to >200 S cm −1 . This provides a soluble analog to the well‐known PEDOT as a new thermoelectric material, as well as a transparent electrode for electrochromic applications.